Real-World Clinical Outcomes and Treatment Patterns Among Black and Non-Black Patients With Prostate Cancer Initiated on Apalutamide in a Urology Setting - Benjamin H. Lowentritt; Carmine Rossi; Erik Muser; Frederic Kinkead; Bronwyn Moore; Patrick Lefebvre; Dominic Pilon; Shawn Du (Journal of Health Economics and Outcomes Research)
**Background:** The use of androgen receptor signaling inhibitors, including apalutamide, in combination with androgen deprivation therapy is recommended for the treatment of metastatic castration-sensitive prostate cancer (mCSPC) and non-metastatic castration-resistant prostate cancer (nmCRPC).